Dividends and Profits: Some Unsubtle Foreign Influences. - Hines, James R (Journal of Finance, 1996)
American corporations earn a significant share of their profits from foreign sources, out of which they appear to pay dividends at rates that are three times higher than their payout rates from domestic profits. Why firms do so is unclear, although this behavior is consistent with the use of dividends to signal profitability. This payout behavior implies that a significant part of the U.S. tax revenue generated by the foreign profits of U.S. corporations arises through the taxation of dividends received by individuals and that the cost of capital may be higher for foreign than for domestic operations.